At a meeting of a number of the citizens of Philadelphia, in the Philosophical Society-Hall, the 8th of November, 1776. Peter Chevalier, chairman : Resolved unanimously, that the following instructions to the representatives of the city of Philadelphia, in Assembly, be published for the consideration of the citizens, previous to a town-meeting to be held at the State-House, the 12th instant, at 9 o'clock in the forenoon. . ([publisher not identified], 1776)
Eight numbered instructions to the Philadelphia representatives to procure modifications in the state constitution of 1776.